1982
DOI: 10.7326/0003-4819-97-6-839
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone Pulmonary Toxicity

Abstract: Pulmonary toxicity may occur in association with amiodarone hydrochloride therapy. The clinical features of the pulmonary involvement are mild dyspnea, leukocytosis, hypoxemia, elevation in the erythrocyte sedimentation rate, and restrictive changes on pulmonary function testing. Diffuse interstitial and patchy peripheral alveolar infiltrates, which may frequently involve the upper lobes, characterize the radiologic findings. Accumulation of foamy macrophages in alveolar spaces, hyperplasia of type II pneumocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1
2

Year Published

1984
1984
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(68 citation statements)
references
References 16 publications
3
62
1
2
Order By: Relevance
“…In some cases various predisposing factors like consanguinity in marriage, pulmonary alveolar proteinosis in siblings, previous infective processes like tuberculosis, fungal diseases. HIV infection, connective tissue diseases and even use of some drugs are present and this group is called secondary [2,4,5,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases various predisposing factors like consanguinity in marriage, pulmonary alveolar proteinosis in siblings, previous infective processes like tuberculosis, fungal diseases. HIV infection, connective tissue diseases and even use of some drugs are present and this group is called secondary [2,4,5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Histologically the material appears granular and eosinophilic and is strongly positive to periodic-acidSchiff (PAS) stain. This is a relatively new disease which was first reported by Rosen ei al in 1 D5B [:1] and by 1DBO only 260 cases were reported in world literature [2]. An open lung biopsy was performed which revealed areas of alveolar exudates, which were granular.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Two of these six patients died. Marchlinski et al (1982) found a 6% incidence of pulmonary changes in their patients. Preliminary data from Greene et al (1982) are of particular concern.…”
Section: Pulmonary Toxicitymentioning
confidence: 92%
“…Sequential changes in pulmonary function tests in patients with severe cardiac disease treated with other antianhythmic drugs have not been reported, thus the role of amiodarone in producing these changes is as yet unknown. Marchlinski et al (1982) described the clinical, radiological, and pulmonary function findings in four patients. All patients had mild dyspnea, leukocytosis, hypoxemia, elevation in the erythrocyte sedimentation rate, and restrictive changes on pulmonary function testing.…”
Section: Pulmonary Toxicitymentioning
confidence: 99%